PERAN KOMPETENSI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI DAN KEPUASAN KERJA ( Studi Pada Sekretariat DaerahKabupaten Rembang ) - Muhammad Luthfi Hakim, 11.42.02.0028 (Students Journal of Economic and Management, 2013)
As we know that human resources, capital, and technology are all factors that are very important in creating a quality product and good governance. In addition to employee competence is an important factor in increasing the motivation and performance of employees there are also other factors that are not less important is transformational leadership. Another factor is no less important in the achievement of organizational goals is motivation and job satisfaction of employees or employee. Phenomena that occur in the District Secretariat Rembang include many consider continuing education as a condition for adjustment only diploma without being followed by the practice in the job. In addition, leadership is not supported by the appropriate educational background makes employees are not motivated to work. Taking the sample used in this study is proportional sampling method, the number of respondents as 104 employees at District Secretariat Apex. Significance value of the test variable and transformational leadership competencies to performance through motivation and satisfaction of the hypotheses are rejected there is no effect on the satisfaction of competence. The results also prove that the variables do not mediate motivation and satisfaction and competence variables of transformational leadership on employee performance Rembang District Secretariat. Keywords       : Competence, Transformational Leadership, Motivation, Satisfaction, Employee Performance